Preaching Activity of Antonii Radyvylovsky in the Context of Ukrainian Baroque Culture - Kovalchuk, Natalia; Stoliar, Maryna; Spivak, Volodymyr (Hybris, 2023)
This article analyzes the preaching activities of Antonii Radyvylovsky in order to distinguish in the preacher’s output the general characteristics of the Baroque period, formed under the influence of other cultures. Particular attention is paid to the humorously ridiculous aspect of the preacher's works, which have not been considered at all before. The source base for the study is the handwritten and printed sermons of Antonii Radyvylovsky from his collections The Fenced Garden of the Virgin Mary and The Crown of Christ. It is concluded that Ukrainian Baroque, while absorbing the main features of European Baroque, had its own characteristics. In this context, the legacy of the prominent XVII century Ukrainian preacher Antonii Radyvylovsky constitutes a typical example of the introduction of Latinizing Christian traditions into the Orthodox liturgy. In the center is a "living" earthly man with his virtues and flaws. The main theme in the moralistic examples in Radyvylovsky's sermons is that of a righteous and sinful (moral and immoral) life. His humorous and satirical discourses allowed Radyvylovsky to develop in his listeners a capacity for a paradoxically Baroque repentance, which is closely tied to personal reflection through laughter.